Quality of Service in the Development of E-Government Systems towards Community Participantion (Case Study of Sinjai Regency Public Service Mall) - Rajamemang, Rajamemang; Ulmi Q, Andi Tenri; Maidin, Andi M Rusdi; Putera, Wahyudi; AB, Fitrawati; Sabir, Muhammad (Jurnal Manajemen Pelayanan Publik, 2025)
This study aims to determine the extent to which the quality of service influences community participation through the E-Government system, with a case study at the Sinjai Regency Public Service Mall. This research employs a qualitative approach conducted through a questionnaire using primary data sources, particularly data obtained from the Sinjai Regency Public Service Mall. The data collection method consisted of questionnaires, observations, and documentation. Questionnaires were distributed to participants, and interviews were conducted with a total population of 255,853 individuals distributed among various villages and sub-district communities. The sample size was determined using the Slovin formula, resulting in a total of 150 respondents. The analysis technique used was Structural Equation Modeling (SEM). The results of the research indicate that service quality, measured through tangibility, reliability, responsiveness, empathy, and assurance, has a positive and significant indirect effect on the E-Government system as well as on community participation at the Sinjai Regency Public Service Mall. Additionally, the E-Government system has a positive and significant effect on community participation in the Public Service Mall of Sinjai Regency.